The Influence of Financial Ratio on Shares Prices of Commercial Banks That Experience Profits on The Indonesian Stock Exchange - Anggraini, Dina; Yuniningsih, Yuniningsih (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2024)
This research aims to determine the effect of Profitability, Market Value, Capital, Asset Quality to the stock price at the commercial banks in the Indonesia Stock Exchange period 2015-2019. The population has been selected by using purposive sampling method at commercial banks which are listed in Indonesia Stock Exchange (IDX) in 2015-2019 periods and based on the predetermined criteria, 17 commercial banks have been selected as samples, while the number of years used are five years, so the sample size is 85 data. The analysis technique used in this research is multiple linear regression analysis and SPSS (Statistical Product and Service Solution) application tool. The result of the research shows that Profitability and Market Value give positive and significant influence on the stock price, Capital gives negative and significant influence on the stock price, and then Asset Quality does not give any significant and positive influence to the stock price.